The Influence of Supervisor’s Support and Protection Against Whistleblowing Decision in The Organizations of Local Government In Indonesia - Priyastiwi Priyastiwi; Abdul Halim (The Indonesian Journal of Accounting Research, 2018)
Abstract: The purpose of this study is to empirically examine the influence of supervisor's support and protection against whistleblowing decision in the organizations of local government in Indonesia. Also, under a condition of superior support and protection, this study examines the effects of auditors' and non-auditor/employees' types of work in the organization of local governments towards the decision on whistleblowing the fraud. This research uses the experimental method to 48 students of Master of Accounting in a large state-owned university. By using four-case scenarios, participants were asked to answer the possibility to whistleblow the fraud that occurred in a local government organization. The results of this research indicate that the employee would be courageous to whistleblow the fraud when they feel supported by their employers. The results also explain the importance of protection for whistleblowers. The results indicate that high protection is still required by the whistleblower to avoid the threat of any retaliation when the supervisor's support is low. Besides, the results reveal that, under the condition of high supervisor's support and protection, auditors would take a higher whistleblowing decision than non-auditors.Abstract: Tujuan dari penelitian ini adalah untuk menguji secara empiris pengaruh dukungan atasan dan perlindungan terhadap keputusan whistleblowing di organisasi pemerintah daerah di Indonesia. Selain itu, di bawah kondisi dukungan dan perlindungan yang kuat, penelitian ini juga menguji pengaruh jenis pekerjaan auditor dan non-auditor/karyawan dalam organisasi pemerintah daerah terhadap keputusan tentang pengungkap fakta penipuan. Penelitian ini menggunakan metode eksperimen untuk 48 mahasiswa Magister Akuntansi di sebuah perguruan tinggi negeri besar. Dengan menggunakan empat kasus skenario, peserta diminta untuk menjawab kemungkinan untuk mengungkap penipuan yang terjadi di organisasi pemerintah lokal. Hasil penelitian ini menunjukkan bahwa karyawan akan berani untuk mengungkap penipuan ketika mereka merasa didukung oleh majikan mereka. Hasilnya juga menjelaskan pentingnya perlindungan bagi pelapor. Hal ini menunjukkan bahwa perlindungan yang kuat masih diperlukan oleh whistleblower untuk menghindari ancaman pembalasan ketika dukungan supervisor rendah. Selain itu, hasil menunjukkan bahwa, di bawah kondisi dukungan dan perlindungan supervisor yang kuat, auditor akan mengambil keputusan whistleblowing lebih tinggi daripada non-auditor.